Determinants of low birth weight in the Lower Manya Krobo Municipality of the Eastern region of Ghana - Larbi, Paul; Dedu, Vincent K.; Okyere, Gabriel A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Low birth weight refers to new borns weighting less than 2.5 kg at birth. In November 2017, the WHO reported a global prevalence of 15.5% with 96.5% of these cases happening in developing countries. Whilst this is a global canker, the risk factors differ from locality to locality. This study aims at determining which maternal factors explains low birth weight baby delivery in the Lower Manya Krobo Municipality. Methods: The chi-square test for independence was used to test for independence. The binary logistic model is fitted for the associated factors. The receiver operating characteristic (ROC) is used to classify unbiased estimators. Results: ANC (yes β= -2.769 sig.=0.000); Alcohol (none β=-1.479 sig.=0.000, occasionally β= −2.043 sig.=0.000); Age (<20years β=0.178 sig. =0.676, 20 to 25years β= -1.487 sig.=0.000, 26 to 30 β= -0.941 sig.=0.086); Education level (None β=2.778 sig. =0.000, primary β=3.090 sig.=0.000, JHS β=1.913 sig.=0.002, SHS/Secondary β=1.951 sig.=0.000); Exposure to Heat (Yes β=4.507 sig.=0.000). AUC education=0.67, 95% CI=0.6,0.7 and AUC Exposure to heat=0.73, 95% CI=0.68,0.77 of low birth weight. Conclusions: Social status was not significant factor. Mothers exposed to heat had the highest risk (odds=90 times). Adolescent mothers stand high risk with odds 1.195. Mothers who attended antenatal clinics were at 94% less likelihood. Mild drinkers had lesser risk compared to no and heavy drinkers. Mothers with primary education (odds=21 times) were the riskiest compared to mothers with tertiary education. This differs from researches where no education mothers were riskiest. Only mother’s exposure to heat was found to be fairly good unbiased estimators.